2017
DOI: 10.31186/jspi.id.12.3.277-289
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Ampas Tahu sebagai Campuran Pakan terhadap Pertumbuhan Cacing Tanah Pheretima sp

Abstract: This study aimed to determine the effect of tofu waste as a feed mixture to the growth of earthworm Pheretima sp. This research was conducted in Bengkulu City and Animal Husbandry Laboratory of Bengkulu University. This research used method of Completely Randomized Design with 4 treatments and 5 replicates: (P1) = Rice husk 50% + Feces of cow 50% + (0% tofu waste), (P2) = Rice husk 50% + Cow feces 45% + (5% tofu waste), (P3) = Rice husk 50% + Cow feces 40% + (10% tofu waste), (P4) = Rice husk 50% + Cow feces 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Thus, the worms get an adequate source of protein as a growth substance (Yulisman et al, 2012). This is following research conducted by Brata et al (2017) which stated that giving tofu dregs as a feed mixture affected the growth of earthworms.…”
Section: The Effect Of Combination Of Tofu Dregs and Coconut Fruit Dr...mentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, the worms get an adequate source of protein as a growth substance (Yulisman et al, 2012). This is following research conducted by Brata et al (2017) which stated that giving tofu dregs as a feed mixture affected the growth of earthworms.…”
Section: The Effect Of Combination Of Tofu Dregs and Coconut Fruit Dr...mentioning
confidence: 93%
“…In terms of temperature measurements, the C growing medium (treatment 2) from day 1 to day 21 ranged from 25°C to 26.9°C. This is by the opinion of Brata et al, (2017) Brata et al, (2017) which states that the optimum temperature for the growth of worms is 21°C to 29°C. Meanwhile, the pH of the growing medium C (treatment 2) ranged from 6.3 to 6.6. according to Hanafiah et al (2005), the best earthworm growth is in a place that has a pH of around 6 to 7.2.…”
Section: The Effect Of Combination Of Tofu Dregs and Coconut Fruit Dr...mentioning
confidence: 98%
“…Additional feeding of tofu dregs can increase the body weight gain of the parent and the body weight of the offspring of Pheretima Sp. for 60 days of care [15]. Furthermore, [16] found that feeding the baglog mushroom waste Pleurotus ostreatus significantly affected the growth and cocoon production of the Lumbricus rubellus.…”
Section: Total Weight Of Lumbricus Rubellusmentioning
confidence: 99%
“…Produksi kokon tertinggi diperoleh pada media campuran sampah organik pasar dengan feses sapi, sedangkan produksi biomassa tertinggi dicapai pada penggunaan campuran sampah organik pasar dan feses kuda (Mashur, 2020). Penambahan ampas tahu pada pakan berpengaruh nyata terhadap bobot badan cacing tanah (Brata, 2017).…”
Section: Berat Total Cacing Tanahunclassified